Programa territórios da cidadania no estado do Ceará: Uma análise do capital humano e capital natural - Canuto, Karen Emanuelle Barbosa (2011)
The program was created territories of citizenship for income generation and poverty reduction of the most vulnerable regions in Brazil. Inside the importance of Citizenship Territories Program, no study was conducted in order to assess the human and natural capital of the territories of the state of Ceara. This study aimed to characterize the municipalities of Ceara entered into the territories of citizenship, especially in the territories Inhamuns / Crateus, Central Hinterland, Hinterland of Caninde and Valleys Curu Aracatiaçu and about their level of human capital and natural. To achieve the research objectives were achieved bibliographic and documentary to understand the objects that were measured: natural and human capital. The analysis of data provided by IBGE and IPECE was originally used to build a socioeconomic profile of each territory. For the construction of the indices of natural capital indicators were used with dimensions for the fauna, rainfall rainfall and arable land, for the human capital dimensions used were related to education and health. Data were provided by INEP, IBGE and IPECE. Then the data were tabulated, analyzed, interpreted and presented in tables, using descriptive statistics. The survey data show that the municipalities are mostly low rate of natural capital, while the results of the human capital index have better results in all municipalities. This is explained by resources from the federal government. While in the area of education are invested 5% and 10% in health, is less than 1% of the funds invested in preserving natural resources. Using the resources to invest in education, health and natural resources preferentially according to the concept of sustainable development will be a reduction in poverty in these territories.